The role of particle radiotherapy in the treatment of skull base tumors - Iannalfi, Alberto; Riva, Giulia; Ciccone, Lucia; Orlandi, Ester (Frontiers in Oncology, 2023)
The skull base is an anatomically and functionally critical area surrounded by vital structures such as the brainstem, the spinal cord, blood vessels, and cranial nerves. Due to this complexity, management of skull base tumors requires a multidisciplinary approach involving a team of specialists such as neurosurgeons, otorhinolaryngologists, radiation oncologists, endocrinologists, and medical oncologists. In the case of pediatric patients, cancer management should be performed by a team of pediatric-trained specialists. Radiation therapy may be used alone or in combination with surgery to treat skull base tumors. There are two main types of radiation therapy: photon therapy and particle therapy. Particle radiotherapy uses charged particles (protons or carbon ions) that, due to their peculiar physical properties, permit precise targeting of the tumor with minimal healthy tissue exposure. These characteristics allow for minimizing the potential long-term effects of radiation exposure in terms of neurocognitive impairments, preserving quality of life, and reducing the risk of radio-induced cancer. For these reasons, in children, adolescents, and young adults, proton therapy should be an elective option when available. In radioresistant tumors such as chordomas and sarcomas and previously irradiated recurrent tumors, particle therapy permits the delivery of high biologically effective doses with low, or however acceptable, toxicity. Carbon ion therapy has peculiar and favorable radiobiological characteristics to overcome radioresistance features. In low-grade tumors, proton therapy should be considered in challenging cases due to tumor volume and involvement of critical neural structures. However, particle radiotherapy is still relatively new, and more research is needed to fully understand its effects. Additionally, the availability of particle therapy is limited as it requires specialized equipment and expertise. The purpose of this manuscript is to review the available literature regarding the role of particle radiotherapy in the treatment of skull base tumors.